2015
DOI: 10.1016/j.dhjo.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Intersections between disability, type of impairment, gender and socio-economic disadvantage in a nationally representative sample of 33,101 working-aged Australians

Abstract: Crude comparisons between people with and without disabilities obscure how disadvantage is patterned according to impairment type and gender. The results emphasize the need to unpack how gender and disability intersect to shape socio-economic disadvantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
79
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 28 publications
9
79
1
Order By: Relevance
“…Our findings correspond with those of previous Australian studies using HILDA and the ABS surveys – the Survey of Disability, Ageing and Carers and General Household Social Survey [12, 22, 3437]. However, this paper adds to the existing literature by covering a broader range of social and economic domains and indicators of health and wellbeing and using an internationally validated instrument to measure disability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our findings correspond with those of previous Australian studies using HILDA and the ABS surveys – the Survey of Disability, Ageing and Carers and General Household Social Survey [12, 22, 3437]. However, this paper adds to the existing literature by covering a broader range of social and economic domains and indicators of health and wellbeing and using an internationally validated instrument to measure disability.…”
Section: Discussionsupporting
confidence: 87%
“…Future analyses could explore a range of different cut-offs and compare outcomes among men with different types of impairments as previous research has shown that people with psychological and intellectual impairments tend to fare worse on socio-economic and health outcomes than people with sensory and speech and physical impairments [12, 22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A physical impairment – broadly defined as a condition that “substantially limits one or more major life activities” (Americans With Disabilities Act of 1990, 1991) is often associated with high levels of stress, great material hardship and socio-economic disadvantage (National Council on Disability, 2008; Kavanagh et al, 2015). Research has also demonstrated that physical impairment is accompanied by higher levels of alcohol use and alcohol-related disorders (Brown, 2015; Brown et al, 2014; Corrigan & Bogner, 2007; Ebener & Smedema, 2011; Turner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that income is lower and the poverty rate higher for the disabled. 4 This is often attributed to lower labor market participation of the disabled person and possibly other members in their household. 5,6 The presence of a disability may create demand for competing goods and services that households with disabled members may trade-off essential food consumption in order to secure.…”
mentioning
confidence: 99%